The Emergence of Public Sector Innovation Associated with Civil Servants' Perception in 3T Regions: Results of a Multiple Regression Analysis - Virgiawan Listanto; Nova Yulanda Putri Sipahutar; Tisa Lestari (Jurnal Borneo Administrator, 2023)
Innovations from civil servants determine government bureaucracy. However, their effectiveness toward the emergence of public sector innovations has not been widely explored, particularly from civil servants' perception of local government institutions in a 3T region. This study examines the civil servants' perception of the emergence of public sector innovations and identifies the factors that influence them. Thirty-nine civil servants of the innovation laboratory WhatsApp group from North Lombok Regency in the 3T regions participated in this study. The data were analysed using descriptive statistics and multiple regression. The result of the study discovered that most civil servants have a positive insight into the emergence of public sector innovations. They perceived that leader are essential in encouraging innovations in the public sector. Their organisational climate is open to new things. However, attention regarding employee rewards after completing work challenges is still lacking. Meanwhile, their organisation has sufficient capacity to encourage job completion. Multiple regression analysis revealed that independent variables (transformational leadership, organisational climate, and organisational capacity) have a 54.9% contribution and simultaneously affect the emergence of public sector innovations. The partial regression coefficient test revealed that organizational climate contributed the most, with a 33.4% contribution to the emergence of public sector innovations. The results of this study provide implications for both academic and government settings, especially in the organisational climate, which turned out to have been significantly affected by the emergence of public sector innovations